Customary Ritual and Islamic Law: Legal Reflections on the Pati Ka Du'a Bupu Ata Mata of the Lio Tribe in Pemo Village - Iskandar Iskandar; Idul Tarsid (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
Pati Ka Du'a Bupu Ata Mata is a ritual of reverence practiced by the Lio tribe, in which offerings are presented to ancestral spirits. These offerings typically include cigarettes, betel nuts, brown rice, chicken, pork, pork heart, and beverages such as moke (palm wine). The ritual concludes with Mosalaki (traditional leaders) and participants consuming part of the offerings. However, the majority of the Lio tribe in Pemo Village have a limited understanding of Islamic teachings. This study aims to examine the practice of Pati Ka Du'a Bupu Ata Mata and assess its compatibility with Islamic law within the Lio tribe community in Pemo Village. A qualitative research approach is employed, with purposive sampling used to select key informants, including Mosalaki, as well as religious and community leaders in Pemo Village, Kelimutu District, Ende Regency. Data for this study were gathered through observation, interviews, documentation, and bibliographic analysis. The research follows a structured data analysis method consisting of data collection, reduction, presentation, and conclusion drawing. The findings reveal that Pati Ka Du'a Bupu Ata Mata is a tradition of offering tribute to deceased ancestors as an expression of gratitude to both the divine and the ancestral lineage that brought life to the present generation. These offerings—brown rice, palm wine (moke), areca nut, liver, and pork heart—serve as a means of strengthening communal ties and honoring heritage. However, from the perspective of Islamic law, this ritual is considered impermissible, as it involves elements of shirk (associating partners with God) and the consumption of pork and palm wine, which are explicitly prohibited in Islam. The implications of this study highlight the importance of religious awareness within the community, encouraging individuals to avoid rituals that conflict with Islamic teachings as prescribed in the Qur'an and Hadith.